The Danish Language in the Digital Age - Rehm, Georg; Uszkoreit, Hans.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
_
Executive Summary -- Languages at Risk: a Challenge for Language Technology -- The Danish Language in the Information Society -- Language Technology Support for Danish -- About META-NET.
Keywords: Computer science; Translators (Computer programs).; Computational linguistics; Computer Science; Language Translation and Linguistics; Computational Linguistics